Nationalism Among Students: A Comparison Between Students of Islamic Junior High School and Students Of Junior High School in Serang Municipality and Serang Regency - Anis Fauzi (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2015)
This article aims to explore the nationalism among students Islamic Junior High School (MTs) and Junior High School (SMP) in the District of Serang and Serang Municipality. Statistical analysis show that in order to find a comparison between the national insight MTs and SMP students in research location by using Test 't' to sample a large group. Based this study, it is concluded that there was no significant difference between the nationalistic viewpoint MTs and SMP students in Serang Municipality with MTs and SMP students in Serang District. However, basing on the difference between the average value the mean between the two groups of respondents turned out to mean price MTs and SMP student groups in Serang City (204.235) were slightly larger than the mean price of MTs and SMP school student groups in the district of Serang (203.765).